Antinociceptive Ecdysteroids and Other Constituents of Palisota hirsuta K. Schum (Commelinaceae) - Francis Mainoo Sarpong, Francis Ackah Armah, Isaac Kingsley Amponsah, Philip Kobla Atchoglo (Journal of Applied Pharmaceutical Science, 2016)
The root of Palisota hirsuta is used in Ghana and other West African countries for the treatment of various disease conditions such as rheumatoid arthritis (also in other inflammatory and painful conditions), infertility in females, anaemia, and dysentery. The current study sought to evaluate the anti-nociceptive effect of the hydroethanolic root extract and compounds isolated from Palisota hirsuta. Mice were used for studying the antinociceptive activity of P. hirsuta extracts and isolates at doses of 10-300 mgkg-1p.o and 10- 30 mgkg-1 respectively using the Formalin Induced paw licking model. The total crude extract, methanolic and petroleum ether fractions showed analgesic activity in a dose-dependent manner for both the early and late phases. Three isolates, a fatty acid mixture, 20-hydroxyecdysone and an uncharacterized ecdysteroid (PH V) were obtained from the methanol fractions with significant activity. 20-hydroxyecdysone exhibited a dose-dependent inhibition of the nociception for both the early and late phases; 71.39±9.19% and 89.19±3.81% respectively. PH V showed significant activity between the early and late phases of inhibition as compared to the reference drug morphine. The present study has given scientific credence to the use of the roots of P. hirsuta for the mitigation of pain and established its antinociceptive constituents.
Keywords: Formalin, Nociceptive, Inhibition, Isolates, ecdysteroids.